Ultrasound Imaging for the Diagnosis and Evaluation of Sarcopenia: An Umbrella Review - Jia-Chi Wang; Wei-Ting Wu; Ke-Vin Chang; Lan-Rong Chen; Shao-Yu Chi; Murat Kara; Levent Özçakar (Life, 2021)
There is an increasing number of reviews investigating the value of ultrasound (US) in the assessment of aging-related muscle loss. The present umbrella review aimed to systematically investigate the evidence of US imaging in the diagnosis and evaluation of sarcopenia. PubMed, Medline, Embase and Web of Science were searched from their inceptions to 31 October 2021. Systematic reviews and reviews using a systematic strategy for literature search were enrolled. The extracted data were narrated at the level of systematic reviews and meta-analyses. This umbrella review included four articles pertaining to 125 original studies and yielded several important findings. First, US is a reliable and valid imaging tool for the assessment of skeletal muscle mass. Second, among all the US parameters in B-mode, muscle thickness is the most commonly used one, which has good correlation with other standard measurements. Third, although sonoelastography and contrast-enhanced US are promising imaging modalities, their clinical utility is still limited at the current stage. Finally, a future systematic review is warranted to analyze how different ultrasonographic diagnostic criteria influence the prevalence of sarcopenia as well as its adverse health outcomes.